A mechanism-based theory of cellular and tissue plasticity - Sun, Fuqiang (2024)
Plastic deformation in cells and tissues has been found to play crucial roles in collective cell migration, cancer metastasis, and morphogenesis. However, the fundamental question of how plasticity is initiated in individual cells and then propagates within the tissue remains elusive. Here, we develop a mechanism-based theory of cellular and tissue plasticity that accounts for all key processes involved, including the activation and development of active contraction at different scales as well as the formation of endocytic vesicles on cell junctions and show that this theory achieves quantitative agreement with all existing experiments. Specifically, it reveals that, in response to optical or mechanical stimuli, the myosin contraction and thermal fluctuation-assisted formation and pinching of endocytic vesicles could lead to permanent shortening of cell junctions and that such plastic constriction can stretch neighboring cells and trigger their active contraction through mechanochemical feedbacks and eventually their plastic deformations as well. Our theory predicts that endocytic vesicles with a size around 1 to 2 µm will most likely be formed and a higher irreversible shortening of cell junctions could be achieved if a long stimulation is split into multiple short ones, all in quantitative agreement with experiments. Our analysis also shows that constriction of cells in tissue can undergo elastic/unratcheted to plastic/ratcheted transition as the magnitude and duration of active contraction increases, ultimately resulting in the propagation of plastic deformation waves within the monolayer with a constant speed which again is consistent with experimental observations.